The promoter of the oocyte-specific gene, Oog1, functions in both male and female meiotic germ cells in transgenic mice. - Miya Ishida; Eriko Okazaki; Satoshi Tsukamoto; Koji Kimura; Akira Aizawa; Seiji Kito; Hiroshi Imai; Naojiro Minami (PLoS ONE, 2013)
Oog1 is an oocyte-specific gene whose expression is turned on in mouse oocytes at embryonic day (E) 15.5, concomitant with the time when most of the female germ cells stop proliferating and enter meiotic prophase. Here, we characterize the Oog1 promoter, and show that transgenic GFP reporter expression driven by the 2.7 kb and 3.9 kb regions upstream of the Oog1 transcription start site recapitulates the intrinsic Oog1 expression pattern. In addition, the 3.9 kb upstream region exhibits stronger transcriptional activity than does the 2.7 kb region, suggesting that regulatory functions might be conserved in the additional 1.2 kb region found within the 3.9 kb promoter. Interestingly, the longer promoter (3.9 kb) also showed strong activity in male germ cells, from late pachytene spermatocytes to elongated spermatids. This is likely due to the aberrant demethylation of two CpG sites in the proximal promoter region. One was highly methylated in the tissues in which GFP expression was suppressed, and another was completely demethylated only in Oog1pro3.9 male and female germ cells. These results suggest that aberrant demethylation of the proximal promoter region induced ectopic expression in male germ cells under the control of 3.9 kb Oog1 promoter. This is the first report indicating that sex-dependent gene expression is altered according to the length and the methylation status of the promoter region. Additionally, our results show that individual CpG sites are differentially methylated and play different roles in regulating promoter activity and gene transcription.